Prevalence of sustained hypertension and obesity among urban and rural adolescents: a school-based, cross-sectional study in North India - Dorairaj Prabhakaran; Kavita Singh; Ambuj Roy; Bishav Mohan; Amit Verma; Kalpana Singh; Sarit Sharma; Raahat Bansal; Rohit Tandon; Abhishek Goyal; Bhupinder Singh; Shibba Takkar Chhabra; et al. (BMJ Open)
Objective Recent data on sustained hypertension and obesity among school-going children and adolescents in India are limited. This study evaluates the prevalence of sustained hypertension and obesity and their risk factors among urban and rural adolescents in northern India.Setting A school-based, cross-sectional survey was conducted in the urban and rural areas of Ludhiana, Punjab, India using standardised measurement tools.Participants A total of 1959 participants aged 11–17 years (urban: 849; rural: 1110) were included in this school-based survey.Primary and secondary outcome measures To measure sustained hypertension among school children, two distinct blood pressure (BP) measurements were recorded at an interval of 1 week. High BP was defined and classified into three groups as recommended by international guidelines: (1) normal BP: <90th percentile compared with age, sex and height percentile in each age group; (2) prehypertension: BP=90th–95th percentile; and (3) hypertension: BP >95th percentile. The Indian Academy of Pediatrics classification was used to define underweight, normal, overweight and obesity as per the body mass index (BMI) for specific age groups.Results The prevalence of sustained hypertension among rural and urban areas was 5.7% and 8.4%, respectively. The prevalence of obesity in rural and urban school children was 2.7% and 11.0%, respectively. The adjusted multiple regression model found that urban area (relative risk ratio (RRR): 1.7, 95% CI 1.01 to 2.93), hypertension (RRR: 7.4, 95% CI 4.21 to 13.16) and high socioeconomic status (RRR: 38.6, 95% CI 16.54 to 90.22) were significantly associated with an increased risk of obesity. However, self-reported regular physical activity had a protective effect on the risk of obesity among adolescents (RRR: 0.4, 95% CI 0.25 to 0.62). Adolescents who were overweight (RRR: 2.66, 95% CI 1.49 to 4.40) or obese (RRR: 7.21, 95% CI 4.09 to 12.70) and reported added salt intake in their diet (RRR: 4.90, 95% CI 2.83 to 8.48) were at higher risk of hypertension.Conclusion High prevalence of sustained hypertension and obesity was found among urban school children and adolescents in a northern state in India. Hypertension among adolescents was positively associated with overweight and obesity (high BMI). Prevention and early detection of childhood obesity and high BP should be strengthened to prevent the risk of cardiovascular diseases in adults.